Faktor yang memengaruhi intensi penggunaan mobile payment berkelanjutan di kalangan Gen Z: Ekstensi dari expectation confirmation model - Kusuma, Fenylia Nurshakira Putri; Rachmawati, Riani (Journal of Youth and Outdoor Activities, 2024)
Background: Indonesia’s fintech industry is rapidly growing, driven by the acceleration of digitalization during the pandemic and positive investor engagement in the Fintech category in ASEAN. Findings: As a developing country with a large unbanked population, the use of m-payments has the potential to help improve financial inclusion through better access to useful and affordable financial services. Methods: This study combines UTAUT2 and ECM to investigate factors that significantly influence the continuance intention in using m-payments among Gen Z as potential target customers in Indonesia. Conclusion: The findings showed that continuance intention to use m-payments was positively influenced by Habit, Hedonic Motivation, Satisfaction, Facilitating Condition. There is also an indirect effect of Performance Expectancy on continuance intentions through the mediation of the Satisfaction. In addition, the study found the mediating role of Performance Expectancy in the relationship between Effort Expectancy and Confirmation on Satisfaction.